Cooperation or conflict over child health surveillance? Views of key actors. - Gillam, S (1993)
OBJECTIVE--To describe the views of general practitioners, health visitors, and clinical medical officers on child health surveillance, recent changes, perceptions of each other's roles, and attitudes to audit. DESIGN--Postal questionnaire survey. SETTING--Three health districts in North West Thames health region. SUBJECTS--All 602 general practitioners, 272 health visitors, and 42 clinical medical officers in these districts. MAIN MEASURES--Attitudes to and perceptions of child health surveillance and audit. Questionnaires were completed by 440 general practitioners (response rate 73%), 164 health visitors (60%), and 39 clinical medical officers (93%). RESULTS--Attitudes to child health surveillance were less positive among general practitioners than health visitors or clinical medical officers. Few respondents agreed that child health surveillance was a cost effective use of general practitioners' time (general practitioners 28%, 113/407; health visitors 28%, 40/145; clinical medical officers 39%, 15/39) and most thought that health visitors should carry out more of the doctors' examinations (68%, 262/387; 65%, 89/136; 66%, 25/38). General practitioners thought that clinical medical officers were less supportive than other relevant groups of their doing more child health surveillance. Most (72%, 105/146) health visitors thought that the 1990 contract had reduced parental choice of where to attend for child health surveillance. General practitioners were less enthusiastic than health visitors about most forms of clinical audit. CONCLUSIONS--Despite reservations about the impact of recent changes all groups were willing to explore innovative ways of delivering child health surveillance. IMPLICATIONS--There is scope for health visitors to increase their responsibilities and for more varied relationships between general practitioners and community child health doctors.